Is your mama a llama - Guarino, Deborah; Kellogg, Steven (New York, N.Y. : Scholastic, 1997)
A young llama asks his friends if their mamas are llamas and finds out, in rhyme, that their mothers are other types of animals.
Cover title.
On board pages.
Keywords: Llamas -- Fiction; Stories in rhyme